The Role of Education in Preventing E-Smoking Behavior is to Increase Student Knowledge and Attitudes - Sri Sunarti; Tukimin bin Sansuwito; Purwo Setiyo Nugroho; Nida Amalia; Rusni Masnina; Linda Suwarni (Journal of Public Health and Pharmacy)
Introduction: Aim this reseach to determine the differences in levels of knowledge, Attitude about e-smoking prevention before and after education between ekperimental and the control group the Samarinda City Central Statistics Agency in 2017 (3). The number of teenage smokers in the city of Samarinda reached 29.69%. While there is a significant level of access to advertisements for cigarettes on television and the internet, 15.7% of people access the internet, and 41.5% of people access electronic cigarettes with their peers.